Application of a new pH-sensitive fluoroprobe (carboxy-SNARF-1) for intracellular pH measurement in small, isolated cells. - Buckler, K; Vaughan-Jones, R (1990)
We report the use of a new pH-sensitive dual-emission fluoroprobe, carboxy-seminaphthorhodafluor-1 (carboxy-SNARF-1) for ratiometric recording of intracellular pH (pHi) in small isolated cells. The method is illustrated with pHi measurement in single type-1 cells (cell diameter approximately 10 microns) isolated from the carotid body of the neonatal rat. Carboxy-SNARF-1 is loaded using bath application of the acetoxymethyl ester. When excited at 540 nm, the fluoroprobe gives strong, inversely related emission signals at 590 nm and 640 nm. Stable ratiometric recordings of pHi can be achieved from a single cell (pHi 8.5-6.5) for up to 50 min. Photo-bleaching of the probe is minimised by illuminating at relatively low light intensity (50 W xenon lamp with 0.2% transmission neutral density filter). The probe can be calibrated in situ using the nigericin technique and this is in good quantitative agreement with the independent null-point technique (extracellular weak acid/weak base application) of Eisner et al. (1989).(ABSTRACT TRUNCATED AT 250 WORDS)